2022
DOI: 10.1590/0001-3765202220210595
|View full text |Cite
|
Sign up to set email alerts
|

Soil pockets phosphatization and chemical weathering of sites affected by flying birds of Maritime Antarctica

Abstract: The majority of ornithogenic soils studied in Antarctica focus on the infl uence of penguins, wherever little reports evaluated the infl uence of fl ying birds on soil genesis. This study aimed to characterize the morphologic, chemic, physic, mineralogic, and micromorphologic ornithogenic soil pockets infl uenced by fl ying birds in Snow Island, Maritime Antarctica. Fifteen soil pockets were selected, described, sampled and analyzed, these sites constitute the main areas with intense long-term terrestrial biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
4
6
0
Order By: Relevance
“…enhancing vegetation growth. 11,33,45,47 Our data (Table 2) agree with Cannone et al, 2 who proposed that in Antarctica, avian influences are more important than all other factors in affecting the soil properties.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…enhancing vegetation growth. 11,33,45,47 Our data (Table 2) agree with Cannone et al, 2 who proposed that in Antarctica, avian influences are more important than all other factors in affecting the soil properties.…”
Section: Discussionsupporting
confidence: 89%
“…44 These results are similar to others reported from elsewhere in Maritime Antarctica. 17,19,33,[45][46][47] Previous studies on Snow Island show that soils on marine terraces have low clay content (<12%); high sand proportions, dominated by coarse sand (>79%); and high coarse (>40%), comprised mainly of rounded pebbles. 5 Campbell and Claridge 1 reported that soils from beach deposits in Antarctica are frequently weakly developed with a predominance of pebbles in the coarse fractions, with the surfaces of boulders and pebbles generally fresh, unweathered, and without the brownish stains usually attributed to release of iron.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations